2021
DOI: 10.1002/eap.2491
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of tree origin and urbanization on invertebrate abundance and tree phenology

Abstract: The ongoing wide‐scale introduction of nonnative plants across the world may negatively influence native invertebrate fauna, due to a lack of coevolved traits related to the novel plants, e.g., unique phytochemicals or shifted phenology. Nonnative plants, specifically trees, are common in urban environments, areas that already pose novel habitats to plants and wildlife through a wide array of anthropogenic factors. For example, impervious surfaces contribute to increased ambient temperatures, the so‐called urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 70 publications
0
35
1
Order By: Relevance
“…However, lower carotenoid bioavailability does not necessarily reflect the direct action of pollution but the result of changes in phenology and invertebrate biomass in polluted habitats (Eeva et al, 2010; Sillanpää et al, 2008). At the European level, it has been shown that the dynamics of insect prey biomass, in particular caterpillars, differ in timing and spatial distribution between urban and non-urban populations (Jensen et al, 2022; Pollock et al, 2017; Seress et al, 2018). Therefore, a diet low in carotenoids, either due to diet quality or quantity, during plumage development (i.e., either during postnatal development in young or post-fledging/breeding moult in juveniles/adults) could contribute to the observed dullness pattern across urban great tits, especially for chicks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower carotenoid bioavailability does not necessarily reflect the direct action of pollution but the result of changes in phenology and invertebrate biomass in polluted habitats (Eeva et al, 2010; Sillanpää et al, 2008). At the European level, it has been shown that the dynamics of insect prey biomass, in particular caterpillars, differ in timing and spatial distribution between urban and non-urban populations (Jensen et al, 2022; Pollock et al, 2017; Seress et al, 2018). Therefore, a diet low in carotenoids, either due to diet quality or quantity, during plumage development (i.e., either during postnatal development in young or post-fledging/breeding moult in juveniles/adults) could contribute to the observed dullness pattern across urban great tits, especially for chicks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the same population, we have previously found evidence for selective disappearance of “ low quality ” birds between fledging and recruitment (Salmón et al, 2017). Nonetheless, juvenile birds usually moult faster than adults and are less efficient in absorbing or utilising dietary carotenoids (Ferns & Hinsley, 2008; Hill, 2002); while this could lead to paler plumage in birds in their first year, compared with older birds, in both urban and forest habitats, the effect might be exacerbated in the urban environment where carotenoid availability is limited compared to the forest and resources often remain lower after the breeding season (Jensen et al, 2022; Pollock et al, 2017; Seress et al, 2018). Although we found habitat differences in colouration in 1 yr birds, these did not persist among birds of 2 yr or older.…”
Section: Discussionmentioning
confidence: 99%
“…We included oak trees as they have been found to be a primary source of caterpillars and modulate the breeding phenology of great tits in forest populations (van Noordwijk et al 1995;Visser et al 2006). We included beech trees as this was by far the most common species within the parks (Jensen et al 2021).…”
Section: Territory Mappingmentioning
confidence: 99%
“…A slight mismatch in caterpillar emergence can have detrimental effects at the population level for lepidopterans, because leaves quickly decrease in water and nitrogen content, while defense compounds increase (van Asch and Visser 2007). In urban areas, non-native tree species differ from natives in phenology; while urban native trees show advanced budburst in relation to their rural counterparts in the Northern hemisphere, urban non-native trees were found to have a delayed phenology compared to native trees within the city (Jensen et al 2021, Appendix S1). Combined with arti cial light at night, ambient temperature has been found to modulate egg-laying phenology of great tits (Dominoni et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation